1989
DOI: 10.1111/j.1751-1097.1989.tb08437.x
|View full text |Cite
|
Sign up to set email alerts
|

KINETIC MODEL OF BACTERIORHODOPSIN PHOTOCYCLE: PATHWAY FROM M STATE TO bR

Abstract: A model of the last parts of the bacteriorhodopsin (bR) photocycle is proposed on the basis of experimental data for the kinetic behavior of the 'O' intermediate during a temperature pulse in distilled water suspension. The model includes the previously proposed (but not well characterized) intermediate 'N' between the 'M' and 'O' states of bR. This intermediate exists in fast temperature-dependent quasi-stationary equilibrium with the red-shifted intermediate 'O' and has a maximum of absorption close to the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
1

Year Published

1990
1990
1995
1995

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 17 publications
3
24
1
Order By: Relevance
“….) (22,28,31,32); (ii) at least two parallel photocycles of slightly different bR molecules (23,28,(33)(34)(35). The present results cannot unequivocally distinguish between the two proposed models.…”
Section: Discussioncontrasting
confidence: 50%
“….) (22,28,31,32); (ii) at least two parallel photocycles of slightly different bR molecules (23,28,(33)(34)(35). The present results cannot unequivocally distinguish between the two proposed models.…”
Section: Discussioncontrasting
confidence: 50%
“…Additionally, back-reactions were considered which were placed in the last part of the photoreaction cycle (Kouyama et al 1988, Fodor et al 1988). Similar conclusions were drawn by Chernavskii et al (1989) from temperature pulse experiments which indicated that the back-reactions from N to M and O to N cannot be neglected (see also Vfir6 and Lanyi 1990;Vfir6 et al 1990; Ames and Mathies 1990). Additionally, a possible branching of the photocycle was discussed.…”
Section: Introductionsupporting
confidence: 57%
“…However, discrete first order processes seem to be sufficient to describe the data if branching and back reactions are introduced (e.g. Maurer et al 1987 a, b;Kouyama et al 1988;Chernavskii et al 1989;Vfir6 and Lanyi 1990). To allow a comparison with data from the literature in the present study, a sum of first order exponentials is used to evaluate the time course of the reaction cycle.…”
Section: Data Evaluationmentioning
confidence: 99%
See 2 more Smart Citations